Pancasila Sebagai Senjata Generasi Muda - Siti Elni; Dinie Anggraeni (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2021)
Pancasila as the state ideology and upholding the ideals of the state. As time goes by, the value of Pancasila can be a weapon against today's challenges. The application of Pancasila values is an obligation for Indonesian citizens as a guide for their life. This study aims to explore and study information about the application of Pancasila values as a weapon against various challenges according to the times. The research method uses a qualitative or descriptive approach. The technique of collecting data and information is done through literature study. So the development of the times, the value of Pancasila must be more and more inherent in everyday life so that it can become a habit and not just fade away. To fight against various challenges, Pancasila acts as a weapon in honor of the heroes who have fought for the Indonesian state. The next generation of young people who will defend Pancasila. Pancasila as the embodiment of life in accordance with the times. A form of belief in the struggle of heroes.